Caracterização textural e estrutural de V 2O 5/TiO 2 obtidos via sol-gel: Comparação entre secagem convencional e supercrítica - Rodella, Cristiane B.; Nunes, Luis A. O.; Saeki, Margarida Juri [UNESP]; Padilha, Pedro M. [UNESP]; Florentino, Ariovaldo O. [UNESP] (FapUNIFESP (SciELO), 2002)
This work describes a modified sol-gel method for the preparation of V 2O 5/TiO 2 catalysts. The samples have been characterized by N 2 adsorption at 77K, x-ray diffractometry (XRD) and Fourier Transform Infrared (FT-IR). The surface area increases with the vanadia loading from 24 m 2 g -1, for pure TiO 2, to 87 m 2 g -1 for 9wt.% of V 2O 5. The rutile form is predominant for pure TiO 2 but became enriched with anatase phase when vanadia loading is increased. No crystalline V 2O 5 phase was observed in the catalysts diffractograms. Two species of surface vanadium observed by FT-IR spectroscopy a monomeric vanadyl and polymeric vanadates, the vanadyl/vanadate ratio remains practically constant.
Textural and structural characterization of V 2O 5/TiO 2 catalysts obtained by the sol-gel method: Comparison between conventional and supercritical drying
Keywords: Catalyst; Sol-gel; Vanadium and titanium oxide; monomer; nitrogen; polymer; titanium dioxide; vanadic acid; vanadium derivative; vanadium pentoxide; vanadyl derivative; adsorption; catalyst; crystallization; gel; infrared spectroscopy; intermethod comparison; methodology; phase transition; species differentiation; surface property; X ray diffraction